2020
DOI: 10.3389/fphys.2020.00704
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Material Tendon Properties in Patients With Proximal Patellar Tendinopathy

Abstract: Introduction: The effect of chronic patellar tendinopathy on tissue function and integrity is currently unclear and underinvestigated. The aim of this cohort comparison was to examine morphological, material, and mechanical properties of the patellar tendon and to extend earlier findings by measuring the ability to store and return elastic energy in symptomatic tendons. Methods: Seventeen patients with chronic (>3 months, VISA-P < 80), inferior pole patellar tendinopathy (24 ± 4 years; male = 12, female = 5) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
1
27
4
Order By: Relevance
“…This support that the changes in the tendinopathic tendon may be related to increased water content more than immediate alteration in the tensile bearing components. In contrast, some studies 7,8 have shown decreased mechanical stiffness in tendinopathic tendons compared to healthy controls. Reduction in loading and pain or a combination might have led to the between‐studies variation in stiffness.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This support that the changes in the tendinopathic tendon may be related to increased water content more than immediate alteration in the tensile bearing components. In contrast, some studies 7,8 have shown decreased mechanical stiffness in tendinopathic tendons compared to healthy controls. Reduction in loading and pain or a combination might have led to the between‐studies variation in stiffness.…”
Section: Discussionmentioning
confidence: 89%
“…Tendinopathic tendons typically display disorganization of the extracellular matrix (increased cellularity; increased proteoglycans, glycosaminoglycans, and water); hypervascularization; and disorganized collagen 5 . Concomitantly, mechanical properties have been reported to both decrease 7,8 or remain unchanged 9‐11 in tendinopathic tendons, although the reason for this discrepancy remains unknown. Therefore, additional investigation on how to restore the mechanical properties of tendon in management of patellar tendinopathy is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile modulus of tendon tissue, however, has been well characterised by elastography or ex-vivo tensile testing ( Coombes et al, 2018 ; Finnamore et al, 2019 ). In tendinopathy the tensile modulus of tendon is reduced, resulting in a less stiff tendon ( Wiesinger et al, 2020 ). Higher stiffness characteristic of scar tissue is also relevant to tendinopathy, but our current knowledge is mostly based on measurements of scar formation in other tissues ( Liu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This compensatory increase in CSA is supported by similar changes in PL stiffness and overall collagen content (Cristi‐Sánchez et al, 2019; Young et al, 2018; Zhou et al, 2014). A larger CSA allows dissipation of mechanical force loading across a greater area, protecting against strain‐related injuries (Wiesinger et al, 2020). Tendinopathy of the PL often occurs at the posterior proximal attachment, which has a smaller CSA (Basso et al, 2001; Pearson & Hussain, 2014; Wiesinger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study showed no difference between men and women, or between young boys and girls, in the measures of tendon stiffness or Young's modulus (O'Brien et al, 2010). Likewise, previous studies showed that while the tendon's mechanical properties were predictive of strain injuries, the sex difference was not (Wiesinger et al, 2020). Given these mixed findings, the definitive causes of increased strain-type injuries in the female human PL are not fully understood.…”
Section: Sex Differences In Patellar Ligament Morphology and Tendinopathymentioning
confidence: 96%